Relocation of hypocenter using Jacobian’s matrix and Jeffreys-Bullen’s velocity model - Faid Muhlis; Risca Listyaningrum; Indriati Retno Palupi (UNEJ e-Proceeding, 2016)
Hypocenter is the center of earthquake that the position can be explained in x coordinate, y coordinate and z (depth). The location of the hypocenter is obtained by calculating the arrival time of wave propagation to station (at least three seismic stations) which is multiplied by the velocity model of the earth. To determination the position of hypocenter is used earth velocity model assuming a homogeneous of the earth. In reality the Earth containing in layers and the increasing of depth will make the material more compact, so it make the value of velocity wave propagates in each medium increase. It is necessary to recalculate the position of the hypocenter, so new position of hypocenter is accordance with the geological conditions. In this paper will use the study site on Java Island area with the amount of data are 19.685 events of tectonic earthquake. The processing using Matlab software with Jacobian’s matrix calculation and using reference of Jeffreys-Bullen’s velocity model. The results show that the relocation of the hypocenter position shifted relative to the southeast, while the depth become shallower.